« Qui m’aime me suive ! » Les archives de Jean-Michel Ribes et du Théâtre du Rond-Point à la Bibliothèque nationale de France - Corinne Gibello-Bernette; Hélène Keller (In Situ)
On 24 October 2023 Jean-Michel Ribes was interviewed by In Situ, an exchange during which he spoke about the way he had created his own archives and then about his career as an author and creator. In 2023 the department of performing arts at the French national library received the archives coming from the Théâtre du Rond-Point, in Paris, for the years 2002 to 2022 when Jean-Michel Ribes was director of this theatre. Shortly afterwards, the library also received the personal papers of Ribes, who, since the 1960s, has been an author, an actor and a cinema and stage director. These two archival groups are representative of the kinds of collections held and managed by the library’s performing arts department, but also present certain particularities. They offer an interesting case study for the analysis of the different problematics that characterise all stages in the cycle of the way such collections are processed, from their initial transfer to their final interpretation and promotion, with material and intellectual processing in between. The gift of the theatre’s archives to the national library was made after more than fifteen years of exchanges between the two institutions, and their transfer reveals much about the way a collection enters the national library: necessary adjustments between the donor and the archivists, documentary choices, identification of gaps in the documentation. Usual conservation practices such as the physical description of documents, applied to the two collections, are confronted with novel interrogations raised by the important proportion of documents that are digitally born. Of course, it is only possible to put forward hypotheses concerning the potential contribution of these collections to research on contemporary theatre, but it seems clear that their intrinsic interest and their quality of being largely unknown up to the present will provide documentation on the work of an author and the activities of a theatre hitherto little studied. It is now up to the archivists to publicise the existence of the archives in order to encourage their appropriation by the world of research.